The effect of workforce diversity toward organizational performance in Mahkota Medical Centre / Mohd Faez Saidi - Saidi, Mohd Faez (Faculty of Business and Management, 2015)
This research was conducted for the purpose of "to study the Effect of Workforce Diversity toward Organizational Performance at Mahkota Medical Centre". The main objective of this research was to identify the relationship of Workforce Diversity towards Organizational Performance, It is part of researcher's intention to provide a few suggestions for expatriates on how the McClelland's Theory of Needs would impact their motivation as expatriates in host country. This research paper is supported by primary and secondary data. As for the primary data, the researcher used questionnaire as a medium to collect information from expatriates in semiconductor industry in Melaka. On the other hand, reliable sources have been used by the researcher as secondary data which main gained from journals and articles. The researcher used Statistical Package for Social Science (SPSS) as a platform to analyzed data gained from the respondents. This research will provide the proof of whether all the independent variables have significant relationship with motivation as expatriates.